STRESS RESISTANCE AND COPING STRATEGIES OF STUDENTS UNDER THE MARTIAL LAW - Lytvynchuk, Nataliia; Rymarchuk, Alina (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2024)
The article is devoted to the problem of students’ stress resistance and their choice of coping strategies. The aim of study was determining the relationship between coping strategies and stress resistance of students in the conditions of martial law. Methods of analysis, systematization and generalization of theoretical material were used to solve the stated problem. The following methods were used in the empirical study: a questionnaire to determine stress resistance (N.V. Kirsheva, N.V. Ryabchykova); the "Coping Test" method (R. Lazarus); methods of mathematical statistics: Spearman’s correlation. The article analyzes the concepts of "stress resistance", "coping strategies", "types of coping strategies". During the study, the problems and difficulties that students have during the educational process were considered and summarized. Stress factors that affect students during martial law are mentioned. The psychological conditions for the development of individual stress resistance are defined, namely: self-regulation, adequate self-esteem, optimism, high motivation for professional activity, low level of personal anxiety, internal locus of control, as well as effective application of coping strategies. The results. The level of stress resistance and the main coping strategies used by students in the conditions of martial law have been found out. The results of the stress resistance study showed that half of the respondents (50%) have a high level of stress resistance; 45% of respondents have an average level of stress resistance; a low level of stress resistance was found in only 5% of respondents. It is noted that more than half of the respondents have an average level of coping strategies. There was clarified the most frequent use of such coping strategies by students as: "Escape/avoidance" (60%), "Search for social support" (55%), "Positive reappraisal" (55%), "Self-control" (52%). Conclusions. According to the studying results, the relationship between coping strategies and students stress resistance was ascertained. With the help of correlation analysis, it was determined the presence of significant direct relationships with the scale "Acceptance of responsibility" (r=0.5178, at p≤0.01) and "Confrontation" (r=0.4338, at p≤0.01), as well as an inverse relationship with the coping strategy "Escape/avoidance" (r=- 0.4226, at p≤0.01).